EFL Teachers’ Lived Experiences on Using Grading System (KMC Journal, 2022)
The Grading System, first used by Yale University in the 18th century for the purpose of descriptive evaluation of the students’ achievement, has now become popular worldwide. This paper explores and analyzes the Grade nine and ten English teachers’ lived experiences of using Grading System (GS) in English language teaching and testing in the institutional schools of Kathmandu. For this, we collected the required information taking phenomenological interview with the five purposively selected teachers of English from five respective institutional schools of Nagarjun Municipality in Kathmandu. The collected information was thematically analyzed using ATLAS.ti 9. The lived experiences of the concerned teachers showed the praxis of arbitrary and systematic use of GS in the researched context. The results reveal that the arbitrary use of GS has negative impact on the students’ classroom participation and teaching learning environment while the systematic use of GS has motivated the students towards learning, and thereby enhanced the teachers’ professional development. The study concludes that there is need for using systematic GS making it even more appropriate and scientific for the betterment of overall teaching and learning of English in particular, and thereby the system of secondary level education as a whole.